Caracterização do defeito superficial “olho de peixe” em ferros fundidos em moldagem de areia verde - Santos, Gabriel Pereira dos (2025)
Cast irons correspond to a class of metallic materials that have high carbon contents, ranging from 2.11% to 4% in their composition, as well as alloying elements such as silicon, manganese and sulfur, making it possible to classify cast irons as gray, nodular, white and malleable. Cast iron is widely used in industry due to its cost-benefit ratio, offering excellent mechanical properties and a low-cost, low-stage manufacturing process. These materials are mostly used in critical sectors such as automotive, aeronautics and infrastructure and therefore require a more rigorous guarantee of structural and surface integrity. This paper presents a detailed characterization of the surface defect known as “fish eye”, which recurs in the green sand casting process using exothermic gloves. This defect manifests itself as a surface discontinuity with a circular and/or oval geometry, and is associated with exogenous non-metallic inclusions that act as heterogeneous nucleation sites. The obtained results made it possible to define the “fish-eye” as a defect that occurs during the mold-metal reaction after pouring due to contamination of the molding sand with fragments of unburned exothermic sleeves, rich in fluorine content, owing to the presence of cryolite and fluorite in their conventional compositions. Based on the determination of the cause and origin of the defect, a technical suggestion was made to mitigate the mechanisms responsible for its occurrence, which could enable continuous process improvement and reduce the scrap rate caused by this surface defect. This study has contributed to the technical and scientific understanding of a common surface defect that recurs in green sand casting using exothermic gloves, which compromises not only the surface of the casting, but the entire microstructure as a result of irregular solidification conditions.